Cultural(ized) Religion and Intolerance: A Comparative Study of Serbia, Italy, and the United Kingdom - Turković, Andrea (Journal of religion in Europe, 2025)
This study examines the relationship between religiosity, secularization, and intolerance toward immigrants across distinct cultural and religious contexts—Italy, Serbia, and the United Kingdom. Using data from the ninth wave of the European Social Survey (2023), linear regression models reveal context-dependent patterns: in Serbia, religiosity is linked to higher intolerance; in Italy, religious affiliation plays a central role; in the UK, culturalized religion correlates with exclusionary attitudes. The findings highlight the complexity of secularization outcomes and the role of religiosity in shaping immigration attitudes, demonstrating their dependence on each country’s unique religious and cultural context.